European literature from romanticism to postmodernism : a reader in aesthetic practice - Travers, Martin (Continuum, 2001)
European Literature from Romanticism to Postmodernism is an anthology of key theoretical writings by the major representatives of the schools and movements of recent European literature. Each chapter is devoted to one particular school of movement from within the broad body of literature, from romanticism, realism and modernism though to the literature of political engagement of the 1920s and 1930s, and the more recent initiative of postmodernism. These texts are approached both on their own terms as individual formulations of the goals and procedures (literary, aesthetic and political) that c.